2023
DOI: 10.3390/v15081719
|View full text |Cite
|
Sign up to set email alerts
|

Viruses of Freshwater Mussels during Mass Mortality Events in Oregon and Washington, USA

Abstract: Freshwater mussels (Unionida) are globally imperiled, in part due to largely unexplained mass mortality events (MMEs). While recent studies have begun to investigate the possibility that mussel MMEs in the Eastern USA may be caused by infectious diseases, mussels in the Western USA have received relatively little attention in this regard. We conducted a two-year epidemiologic investigation of the role of viruses in ongoing MMEs of the Western pearlshell (Margaritifera falcata) and the Western ridged mussel (Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
(80 reference statements)
0
7
0
1
Order By: Relevance
“…We identified 193 -194 nt long type 6 IRESs that share 75-90% nucleotide sequence identity in Crogonang virus 17 isolate CGH03, Crogonang virus 61 isolate CGH03 and Picornavirales sp. isolate HPLV-37 [71, 72]. Their genomes encode proteins that are characteristic of marnaviruses, and the genomic location of the IRESs positions them to promote translation of the ORF2 capsid protein precursor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 193 -194 nt long type 6 IRESs that share 75-90% nucleotide sequence identity in Crogonang virus 17 isolate CGH03, Crogonang virus 61 isolate CGH03 and Picornavirales sp. isolate HPLV-37 [71, 72]. Their genomes encode proteins that are characteristic of marnaviruses, and the genomic location of the IRESs positions them to promote translation of the ORF2 capsid protein precursor.…”
Section: Resultsmentioning
confidence: 99%
“…Type 6i-like IRESs were identified in several members of the Marnaviridae family (order Picornavirales) (Table S12). Marnaviruses infect unicellular aquatic organisms and have monocistronic or dicistronic genomes that encode polyprotein precursors of capsid and non-structural proteins [70] [71,72]. Their genomes encode proteins that are characteristic of marnaviruses, and the genomic location of the IRESs positions them to promote translation of the ORF2 capsid protein precursor.…”
Section: Type 6i-like Iress In Marnavirus Genomesmentioning
confidence: 99%
“…As is known, the diversity of picorna-like viruses and the number of their genomes have been actively expanded in the last decade through the analysis of viromes and transcriptomes of invertebrates (including mollusks) [14,15,17,[24][25][26][27]50,51]. We also managed to uncover a new range of previously unknown picornaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic analysis, including shotgun sequencing, is also employed to identify possible viral infections during mollusk diseases. Thus, during the mass mortality events of unknown etiology among freshwater mussels (Unionida) in the rivers of the USA, several dozen new viruses were identified [15,[25][26][27]. It was shown that some of them, for example, a novel densovirus (Clinch densovirus 1; family Parvoviridae), were epidemiologically linked to morbidity [25].…”
Section: Introductionmentioning
confidence: 99%
“…Информация о гипотетических вирусных геномах ускользает от внимания исследователей. В работе [44] авторы применили приложение CD-HIT-EST [45] для кластеризации и поиска сходства между скаффолдами раздельных геномных сборок при исследовании сообществ РНК-содержащих вирусов с помощью алгоритмов выравнивания нуклеотидных последовательностей. Подход с применением CD-HIT-EST в некоторой степени решает проблему сопоставления геномных сборок без таксономии, но может столкнуть с проблемой, когда одна геномная сборка содержит скаффолд -фрагмент генома какого либо вируса, а другая сборка содержит скаффолд -другой фрагмент этого же вируса.…”
Section: обсуждение результатовunclassified